Differential effects of synthetic estrogen on serum homocysteine levels before and after menopause - Michael C. Reed; Ayako Suzuki; Allison Cruikshank; Mizuki Suzuki; H. Frederik Nijhout (PLoS ONE, 2025)
Homocysteine (Hcy), a sulfur-containing amino acid, is produced in prodigious quantities by the methionine cycle in the liver. Hcy is the major biomarker for cardio-vascular disorders and is associated with many other diseases. In previous work, we have explained why menstruating women have lower serum homocysteine than men due to higher concentrations of estradiol. In this study, we first present epidemiological evidence from NHANES data that synthetic estradiol supplementation lowers serum Hcy in post-menopausal women, but raises Hcy in pre-menopausal women. Secondly, we give an explanation of this puzzling phenomenon using previously developed mathematical models of one-carbon and glutathione metabolism. The simulation analysis demonstrated that the non-monotonic response of glutathione to rising estradiol levels may account for the differing Hcy responses to estradiol supplementation in postmenopausal versus premenopausal women, through activation of cystathionine β-synthase, a key enzyme regulating tissue homocysteine levels. Our findings further highlight the importance of considering menopausal status and synthetic hormone use when evaluating the health effects of homocysteine.